"The NHS is on its knees, someone needs to stand up"—why doctors are running for parliament. (31st May 2017) - Rimmer, Abi
Abstract : Over 30 constituencies in the 2017 general election have a candidate who is medically qualified. Seven of the doctors standing for parliament tell Abi Rimmer what they hope to achieve and why doctors make good politicians